Feed intake, emission of enteric methane and estimates, feed efficiency, and ingestive behavior in buffaloes supplemented with palm kernel cake in the Amazon biome - Amaral Júnior, João Maria do; Martorano, Lucieta Guerreiro; Nahúm, Benjamim de Souza; de Castro, Vinícius Costa Gomes; Sousa, Luciano Fernandes; Rodrigues, Thomaz Cyro Guimarães de Carvalho; da Silva, Jamile Andréa Rodrigues; da Costa Silva, Artur Luiz; Lourenço Júnior, José de Brito; Berndt, Alexandre; e Silva, André Guimarães Maciele (Frontiers in Veterinary Science, 2022)
The use of palm kernel cake as an alternative to conventional ingredients, due to the presence of residual fat, can also reduce methane emissions. The objective of the study was to evaluate, in two different experiments, the effects of palm kernel cake supplementation on feed intake, enteric methane production and estimates, and the ingestive behavior of buffaloes in the Amazon biome. In experiment 1, to evaluate feed intake, methane production, and feed efficiency, 20 crossbred females, dry and empty, with a mean age of 34 months and an initial body weight of 514 ± 69 kg, were supplemented with palm kernel cake for 60 days. The supply was calculated in relation to body weight (BW) in four treatments: 0% (control); 0.25, 0.50, and 1% of palm kernel cake, distributed in a completely randomized design. In experiment 2, to evaluate the ingestive behavior, 24 mixed-breed, dry, and non-pregnant buffaloes supplemented with palm kernel cake were evaluated in the less rainy season (LR) and the wettest season (WS) of the eastern Amazon, distributed in a completely randomized in the same treatments as experiment 1. The inclusion of palm kernel cake in the supplementation increased the feed intake of dry matter and components (MM, OM, CP, NDF, ADF, and EE) (P < 0.01), reducing the production of enteric methane intake (P < 0.01), the ratio per kg of meat produced (P < 0.01) and feed efficiency (P < 0.01), and influenced the ingestive behavior (time grazing, rumination, and idleness) during the day. We suggest that further research be carried out to verify the results and improve the use of this co-product as a methanogenesis mitigator.